Correlation of GLUT4, LEPR, and TNF-α with endometrial receptivity in women with polycystic ovarian syndrome-induced infertility - Dong, Yan; Kong, Wei; Li, Yifei; Liu, Yan; Li, Lin; Li, Yan (Journal of Medical Biochemistry, 2024)
Objective: To analyze the correlation of glucose transporter 4 (GLUT4), leptin receptor (LEPR) and tumor necrosis factor-α (TNF-α) with endometrial receptivity in patients with polycystic ovarian syndrome (PCOS)-induced infertility, so as to provide clinical evidence for future diagnosis and treatment of PCOS-induced infertility. Methods: Forty-two patients with PCOS-induced infertility admitted to our hospital from June 2020 to August 2023 (research group), as well as 35 concurrent cases of simple PCOS (control group) and 32 healthy women (normal group) were selected as the research participants. Peripheral blood GLUT4, LEPR and TNF-α levels were detected in all participants, and the diagnostic value of the three for PCOS in healthy women and for PCOS-induced infertility in PCOS patients was analyzed. In addition, the endometrial thickness and the endometrial blood flow pulsation index (PI) and resistance index (RI) of patients in the research group were measured, and the correlation of GLUT4, LEPR, and TNF-α with endometrial receptivity was discussed. Results: GLUT4 was lower in the research group compared with control and normal groups, while LEPR and TNF-α were higher (P<0.05); the control group showed lower GLUT4 and higher LEPR and TNF-α levels than the normal group (P<0.05). The diagnostic sensitivity and specificity of GLUT4, LEPR and TNF-α combined assay for PCOS-induced infertility in PCOS women were 88.57% and 75.00%, respectively, and those for PCOS in healthy women were 78.57% and 60.00%, respectively (P<0.05). In the research group, GLUT4 was positively correlated with endometrial thickness and negatively linked to RI and PI; while LEPR and TNF-α were negatively associated with endometrial thickness and positively correlated with RI and PI (P<0.05). Conclusions: GLUT4, LEPR and TNF-α are closely related to endometrial receptivity in patients with PCOS-induced infertility, and their combined detection can effectively evaluate the occurrence of PCOS and PCOS-induced infertility.